Trans bodies, trans selves : a resource for the transgender community - Erickson-Schroth, Laura (Oxford ; New York : Oxford University Press, USA, 2014)
"There is no one way to be transgender. Transgender and gender non-conforming people have many different ways of understanding their gender identities. Only recently have sex and gender been thought of as separate concepts, and we have learned that sex (traditionally thought of as physical or biological) is as variable as gender (traditionally thought of as social). While trans people share many common experiences, there is immense diversity within trans communities. There are an estimated 700,000 transgendered individuals in the US and 15 million worldwide. Even still, there's been a notable lack of organized information for this sizable group. Trans Bodies, Trans Selves is a revolutionary resource-a comprehensive, reader-friendly guide for transgender people, with each chapter written by transgender or genderqueer authors. Inspired by Our Bodies, Ourselves, the classic and powerful compendium written for and by women, Trans Bodies, Trans Selves is widely accessible to the transgender population, providing authoritative information in an inclusive and respectful way and representing the collective knowledge base of dozens of influential experts. Each chapter takes the reader through an important transgender issue, such as race, religion, employment, medical and surgical transition, mental health topics, relationships, sexuality, parenthood, arts and culture, and many more. Anonymous quotes and testimonials from transgender people who have been surveyed about their experiences are woven throughout, adding compelling, personal voices to every page. In this unique way, hundreds of viewpoints from throughout the community have united to create this strong and pioneering book. It is a welcoming place for transgender and gender-questioning people, their partners and families, students, professors, guidance counselors, and others to look for up-to-date information on transgender life"--
"Trans Bodies, Trans Selves (TBTS) will be the go-to resource for transgender populations, covering health, cultural and social questions, history, theory, legal issues, and more. It is a place for transgender and gender-questioning people, their partners and families, students, educators, counselors, and others to look for up-to-date information on transgender life. It is intended to become the ultimate commercial resource (approx 500 pp.) on trans health and development for trans populations, serving much the same role as Our Bodies, Ourselves, which is now published for women worldwide"--
Throwing our voices : an introduction / Jennifer Finney Boylan -- Introduction to Media spotlight series / Dallas Denny and Jamison Green -- Introduction to Trans political leaders series / Jamie Roberts and Anneliese Singh -- Section 1. Who we are : Our many selves / Holiday Simmons and Fresh! White ; Race, ethnicity, and culture / Kortney Ryan Ziegler and Naim Rasul ; Immigration / Kate Kourbatova and Elana Redfield ; Disabilities and deaf culture / Syrus Marcus Ware and Zack Marshall ; Religion and spirituality / delfin bautista and Quince Mountain, with Heath Mackenzie Reynolds ; Sex and gender development / Laura Erickson-Schroth, Miqqi Alicia Gilbert, and T. Evan Smith -- Section 2. Living as ourselves : Coming out / Reid Vanderburgh ; Social transition / Heath Mackenzie Reynolds and Zil Garner Goldstein ; Employment / Jessica Lina Stirba, Zil Garner Goldstein, and Cecilia Gentili, with Heath Mackenzie Reynolds, Tobi Hill-Meyer, and Dean Scarborough ; Legal issues / Kylar W. Broadus and Shannon Price Minter -- Section 3. Health and wellness : General, sexual, and reproductive health / Nick Gorton and Hilary Maia Grubb ; Medical transition / Maddie Deutsch ; Surgical transition / Jules Chyten-Brennan ; Mental health services and support / Ruben Hopwood and lore m. dickey ; Mental health concerns / Tamar Carmel, Ruben Hopwood, and lore m. dickey -- Section 4. Our relationships and families. Intimate relationships / Sarah E. Belawski and Carey Jean Sojka ; Sexuality / Tobi Hill-Meyer and Dean Scarborough ; Parenting / Kel Polly and Ryan G. Polly -- Section 5. Life stages : Children / Aidan Key ; Youth / Colt Keo-Meier and Lance Hicks ; Aging / Joe Ippolito and Tarynn M. Witten -- Section 6. Claiming our power : U.S. history / Genny Beemyn ; Arts and culture / Lazlo Ilya Pearlman, Jae D.K. Szeszycki-Truesdell, and Kestryl Cael Lowrey ; Activism, politics, and organizing / Peter Cava -- Afterword.
Includes bibliographical references and index.
Keywords: Transgender people; Gender nonconformity; Gender identity; Transgender people; Transgender people -- Legal status, laws, etc; Family and relationships